A Family Segregating Lethal Primary Coenzyme Q10 Deficiency Due to Two Novel COQ6 Variants - Wang, Na; Zheng, Youmin; Zhang, Lingzi; Tian, Xiong; Fang, Yicheng; Qi, Ming; Du, Juping; Chen, Shuaishuai; Chen, Shiyong; Li, Jun; Shen, Bo; Wang, Lizhen (Frontiers in Genetics, 2022)
Primary coenzyme Q10 deficiency-6 (COQ10D6), as a rare autosomal recessive disease caused by COQ6 mutations, is characterized by progressive infantile-onset nephrotic syndrome (NS) resulting in end-stage renal failure and sensorineural hearing loss (SHNL). Here, we report two Chinese siblings with COQ10D6 who primarily presented with severe metabolic acidosis, proteinuria, hypoalbuminemia, growth retardation and muscle hypotonia and died in early infancy. Using whole-exome sequencing and Sanger sequencing, we identified two rare recessive nonsense mutations in the COQ6 gene segregating with disease in affected family members: c.249C>G (p.Tyr83Ter) and c.1381C>T (p.Gln461Ter), resulting in two truncated protein products. Both mutations are located in a highly conserved area and are predicted to be pathogenic. Indeed, the death of our patients in early infancy indicats the pathogenicity of the p.Tyr83Ter and p.Gln461Ter variants and highlights the significance of the two variants for COQ6 enzyme function, which is necessary for the biosynthesis of Coenzyme Q10 (CoQ10). In conclusion, we discovered a novel compound heterozygous pathogenic variant of the COQ6 gene as a cause of severe COQ10D6 in two siblings. Based on the clinical history and genetic characteristics of the patients, our cases expand the genotypic spectrum of COQ10D6 and highlight the heterogeneity and severity of clinical features associated with COQ6 mutations. For patients with clinical manifestations suggestive of COQ10D6, early testing for COQ6 mutations is beneficial for disease diagnosis and therapeutic interventions as well as disease prevention in future generations.